Salivary Exosomal MicroRNA-486-5p and MicroRNA-10b-5p in Oral and Oropharyngeal Squamous Cell Carcinoma - Cosmin Ioan Faur; Rareș Călin Roman; Ancuța Jurj; Lajos Raduly; Oana Almășan; Horațiu Rotaru; Magdalena Chirilă; Mădălina Anca Moldovan; Mihaela Hedeșiu; Cristian Dinu (Medicina, 2022)
Background and Objectives: The research aimed at evaluating the capacity of salivary exosomal miR-10b-5p and miR-486-5p for oral and oropharyngeal cancer detection. Materials and Methods: The saliva samples were harvested from histopathological diagnosed oral and oropharyngeal squamous cell carcinoma patients and healthy volunteer subjects. The exosomes were isolated by differential ultracentrifugation and quantified by Nano Track Analysis. The microRNAs were extracted and quantified from salivary exosomes by quantitative Real-Time Polymerase Chain Reaction. Results: This research comprised fifty participants. When compared to healthy controls, salivary exosomal miR-486-5p was elevated and miR-10b-5p was reduced in oral and oropharyngeal squamous cell carcinoma. Moreover, miR-486-5p had a high expression level in stage II of cancer in comparison to the other cancer stages. The cancer samples presented an increased exosome dimension compared to the control samples. Conclusions: Salivary exosomal miR-10b-5p and miR-486-5p have an altered expression in oral and oropharyngeal cancer.